AN ANALYSIS ON POVERTY INEQUALITY IN SOUTH SULAWESI -INDONESIA BY USING IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Abdul Kadir Arno; Fasiha Fasiha; Muh. Ruslan Abdullah; Ilham Ilham (I-Finance Journal, 2019)
This article provides an overview of economic inequality and the disparity in the level of poverty in the South Sulawesi-Indonesia Province by using variables of economic growth, GDP / capita and the number of poor people between districts in South Sulawesi Province with periodic data types, namely data from 2013-2017. This study uses an Importance-Performance Analysis analysis tool which emphasizes more on quadrant analysis using Cartesian Quadrant. The conclusion of this study is that the disparity of poverty between districts in South Sulawesi Province with determinants of polarized economic growth with high economic growth conditions but the number of poor people is also very high, high economic growth The number of poor people is low, Economic Growth Low the number of poor people is also low , Economic growth is low but the number of poor people is very high, so the determinant of GDP / capita follows the same pattern.